(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
The paper presents preliminary experimental works on a twin-screw compressor to validate and demonstrate piezoelectric energy harvesting. The experiments target an industrially relevant environment: a test bench for industrial air and gas compressors. This work was only possible after previous studies assessing the piezoelectric harvester’s behavior, considering essential factors. In our case, a high working temperature may negatively influence the piezoelectric response and can even damage the material; hence, it should be avoided as much as possible. The piezoelectric harvester’s resonant frequency ought to be adjusted in real-time to match as closely as possible the target vibration frequency of the male rotor, of 83 Hz. We obtained a voltage peak response of 4 VAC and a maximum measured RMS current of 515 µA. The RMS power, calculated at about 1.5 mW, was deemed very satisfactory for a piezoelectric device.